Understanding spirituality from the perspectives of Jordanian people diagnosed with end stage renal failure: a phenomenological study - Tamimi, Abdelrhman Mohammad (2015)
Spirituality has been increasingly acknowledged in nursing literature as an important element of holistic care provision. The literature to date has investigated the meaning of spirituality in Western cultures, predominantly through positivist methodologies. Spirituality in Middle Eastern countries remains under-researched, and this study aims to address this gap and to better understand this concept. The main aim was to understand and interpret patients’ perceptions, experiences, beliefs and practices associated with spirituality by exploring how spirituality is manifest in the lives of Jordanian End Stage Renal Failure (ESRF) patients.